THE EFFECT OF ATTITUDE OF THE ADVERTISING OF WARDAH HALAL COSMETICS ON BEHAVIORAL INTENTIONS - Bunga Permata Samodra; Ririn Tri Ratnasari (Universitas Airlangga, 2020)
Attitude is suggested to have a link to behavioral intention. This study examines the said information, using Wardah advertisement as a research object. Cosmetics and beauty products have been viewed as something essentials nowadays, brought about by the ease of a someone’s image shared on social media. Moreover, an advertisement from halal beauty products like Wardah which upholds Islamic values will generate positive attitude among Muslims. This attitude would affect customer’s behavioral intention. Using quantitative method and questionnaires which were distributed to Muslim female college students, it can be concluded that a person’s attitude towards Wardah advertisement relates to their behavioral intentions toward mentioned product. Kata kunci: Attitude, Behavioral Intention, Halal Cosmetics and Beauty Products, Islamic Advertising